A Numerical and Experimental Investigation of the Effect of False Vocal Fold Geometry on Glottal Flow - Farahani, Mehrdad H. (American Society of Mechanical Engineers, 2013)
The false vocal folds are hypothesized to affect the laryngeal flow during phonation. This hypothesis is tested both computationally and experimentally using rigid models of the human larynges. The computations are performed using an incompressible Navier–Stokes solver with a second order, sharp, immersed-boundary formulation, while the experiments are carried out in a wind tunnel with physiologic speeds and dimensions. The computational flow structures are compared with available glottal flow visualizations and are employed to study the vortex dynamics of the glottal flow. Furthermore, pressure data are collected on the surface of the laryngeal models experimentally and computationally. The investigation focuses on three geometric features: the size of the false vocal fold gap; the height between the true and false vocal folds; and the width of the laryngeal ventricle. It is shown that the false vocal fold gap has a significant effect on glottal flow aerodynamics, whereas the second and the third geometric parameters are of lesser importance. The link between pressure distribution on the surface of the larynx and false vocal fold geometry is discussed in the context of vortex evolution in the supraglottal region. It was found that the formation of the starting vortex considerably affects the pressure distribution on the surface of the larynx. The interaction of this vortex structure with false vocal folds creates rebound vortices in the laryngeal ventricle. In the cases of small false vocal fold gap, these rebound vortices are able to reach the true vocal folds during a time period comparable with one cycle of the phonation. Moreover, they can create complex vorticity patterns, which result in significant pressure fluctuations on the surface of the larynx.